Pelaksanaan Multi Akad (Murabahah dan Rahn) Pada Produk Cicil Emas Menurut Fatwa DSN MUI Pada PT. Bank Sumut Syariah Cabang Stabat - Dwi Rara Amiyati, Ahmad Fuadi, Asmawarna Sinaga (Pusdikra Publishing, 2022)
This study focuses on the discussion on the Implementation of Multi Contracts (Murabahah and Rahn) in Gold Installment Products According to the DSN MUI Fatwa at PT. Bank SUMUT Syariah Stabat Branch. The research method used in this study is a descriptive qualitative research method with an empirical approach. The results of the study explain the procedures for Cicil Emas PT. Bank SUMUT Syariah Stabat Branch are as follows: customer application, collateral assessment, preparation of memorandum of financing analysis, termination of financing, execution of financing agreements, disbursement of financing, procurement of gold, settlement of financing, storage/placement of collateral, execution of collateral, inspection of collateral, process of installment financing gold. Gold Installment Products PT. Bank SUMUT Syariah Stabat Branch uses multiple contracts, namely murabahah and rahn. A murabahah contract occurs between the customer and the Islamic banking institution in the case of buying gold installments, where the bank informs the amount of profit that the bank gets for purchasing the goods requested by the customer. The bank binds the gold as collateral for the gold financing itself using a rahn contract. According to the Fatwa DSN MUI, the implementation of gold installment products that occurred at PT. Bank SUMUT Syariah Stabat Branch in general according to Islamic law. Conduct transactions in the form of murabahah contracts and rahn contracts where Islamic banks as gold providers wish to be owned by customers with guarantees bound by rahn contracts. The use of the two contracts is included in the type of hybrid contract. The original law of a hybrid contract is the same as a single contract, it can be legal or it can be fasid. The prohibition of hybrid contracts as contained in the hadith is not absolute. As long as the merging of these contracts does not contain prohibited elements such as gharar/jahalah and does not lead to elements of usury, then the hybrid contract is legal according to fiqh. The use of two contracts for gold installment products is included in the type of hybrid contract where the contracts do not mix and do not create a new contract name.